Scleritis and Takayasu’s disease – rare combined presentation - Chaudhary, Meenu; Shah, D N; Chaudhary, R P (Nepalese Journal of Ophthalmology, 2018)
Introduction: Takayasu’s disease (TD) (pulseless disease, aortic arch syndrome) is a rare but potentially life-threatening chronic giant cell vasculitis. The major complications attributed to the disease include Takayasu’s retinopathy, secondary hypertension, aortic regurgitation, and arterial aneurysm. The aim of this study is to describe a patient with Takayasu’s disease and scleritis and to show its association. Case report: We describe a 44-year-old female patient with Takayasu’s disease who presented with bilateral anterior scleritis in the form of painful red eye. Patient did not have any associated autoimmune diseases. Patient was diagnosed to have TD and was treated with immunosuppressant. Conclusion: Scleritis though rare can be a vasculitic feature of TD. This is a first report of Takayasu’s disease with scleritis, which has been documented in Nepal.